Enhancing clinical nutrition, glycaemic, appetite and gastrointestinal responses of white rice - Alshammari, Norah (2024)
Background: Rice is staple food for over half the world’s population, with approximately 480 million tonnes consumed annually. High consumption of white rice has been linked with high obesity rates and increased risk for type 2 diabetes. Controlling the properties of white rice products (e.g. reducing the glycaemic index (GI) and/or reducing appetite) with relatively simple interventions could contribute to producing foods with health-promoting profiles. One way to reduce the GI of white rice could be through processing. Addition of hydrocolloids has previously been shown to reduce the digestibility of foods.